Análise comparativa de aços ARBL usados na fabricação de tubos flexíveis para produção de petróleo no mar, em formações com baixo teor de H2S : um estudo de FPH utilizando solução de tiossulfato de sódio - Girelli, Rosental Alves (2006)
This document is an experimental study of the Stress Corrosion Cracking (SCC) and Hydrogen Embrittlement (HE) behavior of a Brazilian high-strength low-alloy steel, in media with low content of H2S. It is intended to begin a qualification process of the material, which is already used in flexible pipes for petroleum production operations at the sea in situations where there is no H2S presence, to also act in cases where low concentration of this gas exists. A heat treatment is proposed for the resistance improvement of the material in these environments. The base for experimental results comparison was another material, a French one, which is already qualified and used in flexible pipes for sour oil (with H2S) production. Hence, three materials were tested: the original Brazilian one, without heat treatment (it is used in flexible pipes, in situations without H2S), the same material with the heat treatment suggested for the property improvement and possible use in low H2S environments and the French one (qualified material used in flexible pipes for oil production operations, in situations where the presence of H2S is a reality). The SCC Slow Strain Rate and Constant Strain techniques were used as the experimental tests and the media was an aqueous solution of NaCl with micro addictions of sodium thiosulfate (Na2S2O3), indicated to simulate corrosive environments with low concentration of H2S. Damage parameters (energy), embrittlement measurements, tensile properties and also fracture features of the specimens were evaluated at the comparative analysis of the materials.